2013
DOI: 10.1007/s12529-013-9341-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Associations of Perceived Stress and Coping Strategies with C-Reactive Protein in Middle-Aged and Older Men and Women

Abstract: Both perceived stress and coping strategies may be associated with systemic inflammation in Japanese men, yet caution must be exercised before accepting the stress-inflammation-disease pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 42 publications
4
39
0
2
Order By: Relevance
“…These findings are consistent with previous studies showing that blood-based biomarkers of inflammation and insulin resistance are related to positive affect/happiness (Matsunaga et al, 2011;Steptoe et al, 2008), well-being (Boehm & Kubzansky, 2012;Osama & Shehab Ael, 2015;Phillips & Perry, 2015;Steptoe et al, 2012), optimism (Ikeda et al, 2011;Roy et al, 2010), psychological resilience or 'hardiness' (Fields, Hoyt, Linnville, & Moore, 2015;Sandvik et al, 2013), and perceived stress (Aschbacher et al, 2013;BarbosaÀLeiker et al, 2014;Shimanoe et al, 2014). Although longitudinal research is needed, our findings suggest the possibility that resilience, optimism, happiness, and low perceived stress might serve as protective factors against insulin resistance and inflammation and their associated negative health outcomes in both schizophrenia and HCs.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous studies showing that blood-based biomarkers of inflammation and insulin resistance are related to positive affect/happiness (Matsunaga et al, 2011;Steptoe et al, 2008), well-being (Boehm & Kubzansky, 2012;Osama & Shehab Ael, 2015;Phillips & Perry, 2015;Steptoe et al, 2012), optimism (Ikeda et al, 2011;Roy et al, 2010), psychological resilience or 'hardiness' (Fields, Hoyt, Linnville, & Moore, 2015;Sandvik et al, 2013), and perceived stress (Aschbacher et al, 2013;BarbosaÀLeiker et al, 2014;Shimanoe et al, 2014). Although longitudinal research is needed, our findings suggest the possibility that resilience, optimism, happiness, and low perceived stress might serve as protective factors against insulin resistance and inflammation and their associated negative health outcomes in both schizophrenia and HCs.…”
Section: Discussionsupporting
confidence: 92%
“…The last two categories were merged in the analysis because of the small number of incident colorectal cancer cases. The one-year test-retest reliability of this question was fair to good21 (weighted κ  = 0.55)22, which is similar to that reported in the INTERHEART study (weighted κ  = 0.53)23.…”
Section: Methodssupporting
confidence: 83%
“…Another measurement problem is the use of a single question to measure perceived stress in the present study. The single-item measure used in the present study showed fair to good test-retest reliability22 and satisfactory content, criterion, and construct validity35. However, compared with a multiple-item measure, a single-item measure is more influenced by random measurement error, which leads to a decrease in the power to detect a true effect36.…”
Section: Discussionmentioning
confidence: 59%
“…Five coping behaviors were extracted from a dispositional version of the General Coping Questionnaire or the Brief COPE, and were assessed using one question: “How do you cope with various problems and unfavorable events you experience in daily life?” Participants answered this question by indicating the frequency (from 4 response categories: “seldom,” “sometimes,” “often,” “very often”) at which they use each of the following coping strategies: (1) “I express my negative feelings and thoughts”, (2) “I consult with someone close and ask for encouragement”, (3) “I try to interpret the problem in a favorable way”, (4) “I try hard to solve the problem” and (5) “I let the problem take its own course.” These coping behaviors were defined as “emotional expression,” “emotional support seeking,” “positive reappraisal,” “problem solving” and “disengagement,” respectively. The weighted kappa based on the 1‐year reproducibility survey was 0.41 for emotional expression, 0.49 for emotional support seeking, 0.30 for positive reappraisal, 0.48 for problem solving and 0.31 for disengagement . Because each coping behavior was examined as an ordinal variable, not a continuous variable following the normal distribution, the levels of each coping behavior were dichotomized to be included as an outcome variable in a mixed linear model, under the assumptions of the liability threshold model .…”
Section: Methodsmentioning
confidence: 99%
“…Perceived stress in daily life was assessed by a single question: “How much stress did you feel during the last year?” Participants chose from 4 response categories: (1) “I felt much stress”, (2) “I felt moderate stress”, (3) “I felt little stress” and (4) “I felt no stress at all.” The perceived stress level was classified as “high” for categories 1 and 2, and “low” for categories 3 and 4. The weighted kappa statistic for this question was 0.55 in a 1‐year reproducibility survey on a random sample ( N = 431) of study participants …”
Section: Methodsmentioning
confidence: 99%